Quality and effectiveness of different approaches to primary care delivery in Brazil - Trindade Thiago G; Goncalves Marcelo R; Cunha Carlo RH; Stein Airton T; Duncan Bruce B; Harzheim Erno; Oliveira Mônica MC; Pinto Maria Eugênia B (BMC, 2006)
Abstract Background Since 1994, Brazil has developed a primary care system based on multidisciplinary teams which include not only a physician and a nurse, but also 4-6 lay community health workers. This system now consists of 26,650 teams, covering 46% of the Brazilian population. Yet relatively few investigations have examined its effectiveness, especially in contrast with that of the traditional multi-specialty physician team approach it is replacing, or that of other existing family medicine approaches placing less emphasis on lay community health workers. Primary health care can be defined through its domains of access to first contact, continuity, coordination, comprehensiveness, community orientation and family orientation. These attributes can be ascertained via instruments such as the Primary Care Assessment Tool (PCATool), and correlated with the effectiveness of care. The objectives of our study are to validate the adult version of this instrument in Portuguese, identify the extent (quality) of primary care present in different models of primary care services, and correlate this extent with measures of process and outcomes in patients with diabetes, hypertension and coronary heart disease (CHD). Methods/Design We are conducting a population-based cross-sectional study of primary care in the municipality of Porto Alegre. We will interview a random sample totaling 3000 adults residing in geographic areas covered by four distinct models of primary care of the Brazilian national health system or, alternatively, by one nationally prominent complementary health care service, as well as the physicians and nurses of the health teams of these services. Interviews query perceived quality of care (PCATool-Adult Version), patient satisfaction, and process indicators of management of diabetes, hypertension and known CHD. We are measuring blood pressure, anthropometrics and, in adults with known diabetes, glycated hemoglobin. Discussion We hope to contribute not only by validating the PCATool-Adult Version for use in Brazil, but also by furnishing ample data concerning the appropriate mix of health care professionals in the primary care team, a question of international import. Once validated, future use of this instrument should help direct advances aiming at improving the quality of primary care in Brazil.